No association between catalase (CAT) gene polymorphisms and susceptibility to vitiligo in a Turkish population - Akbas, H.; Dertlioglu, S. B.; Dilmec, F.; Balkan, M. (Soc Editrice Univ, 2013)
Background and Aims. Vitiligo is an acquired hypomelanotic skin disorder resulting from the loss of functional melanocytes from the cutaneous epidermis. Low catalase (CAT) activity and Accumulation of hydrogen peroxide (H2O2) have been demonstrated in the epidermis of vitiligo patients. Some polymorphisms on catalase gene may have effect on the quantity and activity of catalase enzyme. The aim of this study was to investigate whether catalase (CAT) gene polymorphisms are associated with susceptibility to vitiligo in Turkish population. Materials and Methods. One hundred and three patients with vitiligo and one hundred and seven gender, age and ethnic matched controls were enrolled in the study. Genotyping was done by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP). Results. The CAT gene -89A>T (rs7943316) and 389C>T (rs769217) genotypes and allele frequencies of vitiligo patients did not differ significantly from those of healthy controls. Conclusions. We found no association between CAT gene -89A>T and 389C>T polymorphism and vitiligo susceptibility in Turkish vitiligo patients. Further studies with greater sample size should be performed to verify these results.
Keywords: catalase gene; PCR-RFLP; vitiligo